‘Constellations’ and ‘Entanglement’ in The Study of Legal Pluralism: Reflections on The Scholarship of Keebet Von Benda-Beckmann - Mahy, Petra K, Dr (UI Scholars Hub, 2024)
Two key terms permeate the work of Keebet von Benda-Beckmann (and of her co-authors, especially Franz von Benda-Beckmann) in her discussions of legal pluralism: ‘constellations’ and ‘entanglement’. These terms are both concerned with describing the existence of, and interrelationships between, plural legal orders. This article critically analyses these two terms, their usage and implied meanings, and compares them with other alternative concepts employed elsewhere in legal pluralism and cognate literature. With reference to empirical evidence on plural work regulation in Indonesia, I argue that the terms have some descriptive benefits for understanding the realities of plural legal orders, but still leaves many aspects under-theorised.